Pembobotan Atribut PSO Untuk Klasifikasi Data Kinerja Akademik Mahasiswa - Sri Mujiyono; Suamanda Ika Novichasari (Universitas Ngudi Waluyo, 2018)
An educational database containing information about students is useful for predicting student academic performance. Mujiyono, Sri in 2017 has proven that PSO improves SVM performance for predicting student academic performance. This study aims to prove that PSO can improve the performance of the NBC, C4.5, SVM and NN classification methods for the classification of student academic performance. The results of this study prove that PSO can improve the performance of all the classification methods used. With PSO optimization, NN defeats the accuracy of SVM.